Cryptography and coding 13th IMA International Conference, IMACC 2011, Oxford, UK, December 12-15, 2011. Proceedings - IMA International Conference 2011 Oxford, England); Chen, Liqun; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 13th IMA International Conference on Cryptography and Coding, IMACC 2011, held in Oxford, UK in December 2011. The 27 revised full papers presented together with one invited contribution were carefully reviewed and selected from 57 submissions. The papers cover a wide range of topics in the field of mathematics and computer science, including coding theory, homomorphic encryption, symmetric and public key cryptosystems, cryptographic functions and protocols, efficient pairing and scalar multiplication implementation, knowledge proof, and security analysis.
Electronic reproduction.
Keywords: Data encryption (Computer science) -- Congresses; Computer security -- Congresses